2013
DOI: 10.1590/s0100-69162013000400009
|View full text |Cite
|
Sign up to set email alerts
|

Crop residues on short-term CO2 emissions in sugarcane production areas

Abstract: ABSTRACT:The proper management of agricultural crop residues could produce benefits in a warmer, more drought-prone world. Field experiments were conducted in sugarcane production areas in the Southern Brazil to assess the influence of crop residues on the soil surface in short-term CO 2 emissions. The study was carried out over a period of 50 days after establishing 6 plots with and without crop residues applied to the soil surface. The effects of sugarcane residues on CO 2 emissions were immediate; the emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…However, CO 2 from decomposition of residues is not counted in studies that produce inventories of GHG emission in agriculture, because this CO 2 (biogenic) is cycled in the soil-plant-atmosphere continuum and it is distinguished from CO 2 emitted from fossil fuels used for energy production, which accumulates in the atmosphere (Pourhashem et al, 2013). Nevertheless, crop residue harvest could favor CO 2 emissions, due to the increase in temperature and reduction of moisture in the soil (Corradi et al, 2013;Guzman et al, 2015). The harvest of crop residues over the years should reduce organic C in the soil that could cause significant implications for CO 2 emissions (Six et al, 2004).…”
Section: Impact Of Crop Residues On Ghg Emissionsmentioning
confidence: 99%
“…However, CO 2 from decomposition of residues is not counted in studies that produce inventories of GHG emission in agriculture, because this CO 2 (biogenic) is cycled in the soil-plant-atmosphere continuum and it is distinguished from CO 2 emitted from fossil fuels used for energy production, which accumulates in the atmosphere (Pourhashem et al, 2013). Nevertheless, crop residue harvest could favor CO 2 emissions, due to the increase in temperature and reduction of moisture in the soil (Corradi et al, 2013;Guzman et al, 2015). The harvest of crop residues over the years should reduce organic C in the soil that could cause significant implications for CO 2 emissions (Six et al, 2004).…”
Section: Impact Of Crop Residues On Ghg Emissionsmentioning
confidence: 99%
“…In Brazil, short‐term studies have demonstrated that the removal of sugarcane straw increases soil CO 2 emissions (Corradi et al ., ; Teixeira et al ., ; De Figueiredo et al ., ). Such emissions respond to exponential increases in soil temperature (Davidson et al ., ), which in turn have a remarkable effect on the microbial activity that induces the decomposition of SOM and roots (Silva‐Olaya et al ., ).…”
Section: Impacts Of Straw Removal On Soil Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Corradi et al . () evaluated the effect of straw removal on soil CO 2 emissions. This study observed emissions of 4.1, 3.8, and 5.5 Mg CO 2 ha −1 for areas with 0%, 50%, and 100% straw removal, respectively.…”
Section: Impacts Of Straw Removal On Soil Greenhouse Gas Emissionsmentioning
confidence: 99%
“…They suggested that the impact of minimum and reduced tillage on organic C loss was lower than that observed for conventional operation. A study by Corradi et al (2013) on green cane harvest showed higher CO 2 emissions with no crop residues on the soil surface (bare soil) compared to soil covered with straw. The authors concluded that the conservation of sugarcane crop residues on the soil after harvest could have an impact on soil C conservation.…”
Section: Introductionmentioning
confidence: 99%